An international comparison of school systems based on social mobility - Gaudin, Mattéo; Hindriks, Jean (Economie et Statistique / Economics and Statistics, 2018)
We propose an international comparison of school systems in Oecd countries in terms of social mobility in schools based on the PISA (Program for International Student Assessment) test results in mathematics between 2003 and 2015. For each country, we calculate students' interdecile social mobility in schools on the basis of their ranking in the PISA test in mathematics, compared to their social ranking in their country, and compare this new index of equity to those generally used in Oecd studies (slope and intensity of social gradient, percentage of resilient students). A new representation, the “Great Gatsby curve of school”, in reference to the Great Gatsby curve of income, is proposed: the social mobility of a school system is closely linked to the educational inequality between students and schools. Countries such as Belgium or France with high levels of school inequality also stand out for low social mobility in schools. Inversely, countries such as Finland or Canada are characterised by low school inequality and high levels of social mobility in schools. A second important conclusion of the analysis is that the countries in which social mobility in schools is above average are also most often those with school achievement levels above the average.